Hubungan Partisipasi Ibu Balita Ke Posyandu Dengan Kenaikan Berat Badan Balita Di Desa Sumberberas Kecamatan Muncar Banyuwangi Jawa Timur Periode Mei-Oktober Tahun 2019 - tria eni rafika devi; Kursih Sulastriningsih; Ella Nurlelawati (Akademi Keperawatan RSPAD Gatot Soebroto, 2020)
Posyandu is an important tool in the community that supports efforts to achieve nutri-tionally aware families (KADARZI), helps reduce infant mortality and birth, and accelerates the acceptance of norms of happy and prosperous small families. However, in reality many posyandu members in the community themselves do not use posyandu to monitor their chil-dren's growth and development on the grounds of being busy working or not being able to bring their toddlers to the posyandu and lack of knowledge about the importance of monitoring growth and development in children under five. So a study was conducted aimed at finding out the relationship between the participation of mothers of children under five to posyandu with the weight gain of children under five. This research is observational with cross sectional ap-proach. Data on the participation of mothers of children under five to the posyandu and the weight of children under five is taken directly from the records of KMS and Posyandu Infor-mation Systems (SIP) for children under five in the posyandu. Analysis of the data used is the Chi-Square test. There is a relationship between the participation of mothers of children under five to the posyandu with the weight gain of children under five with a P value of 0.005. Where as seen from the last six months the participation of mothers of toddlers who actively came to the posyandu was 93.9% and those who were not active 61%, the weight of toddlers who rose by 78.8% and those who did not increase by 21.2%, there was a relationship between partici-pation to posyandu with weight gain. The results of this study can be information and input for PUSKESMAS Sumberberas Muncar Banyuwangi East Java village to provide guidance on the benefits of active participation of children under five to the Posyandu and can be used as a ref-erence to develop further research related to the participation of mothers under five to Posyan-du with weight gain under five. .